Electrospray-Based Microencapsulation of Epigallocatechin 3-Gallate for Local Delivery into the Intervertebral Disc - Moira Loepfe; Anja Duss; Katerina-Alexandra Zafeiropoulou; Oddny Björgvinsdóttir; Matteo D'Este; David Eglin; Giuseppino Fortunato; Juergen Klasen; Stephen J. Ferguson; Karin Wuertz-Kozak; Olga Krupkova (MDPI AG, 2019)
Locally delivered anti-inflammatory compounds can restore the homeostasis of the degenerated intervertebral disc (IVD). With beneficial effects on IVD cells, epigallocatechin 3-gallate (EGCG) is a promising therapeutic candidate. However, EGCG is prone to rapid degradation and/or depletion. Therefore, the purpose of this study was to develop a method for controlled EGCG delivery in the degenerated IVD. Primary IVD cells were isolated from human donors undergoing IVD surgeries. EGCG was encapsulated into microparticles by electrospraying of glutaraldehyde-crosslinked gelatin. The resulting particles were characterized in terms of cytocompatibility and anti-inflammatory activity, and combined with a thermoresponsive carrier to produce an injectable EGCG delivery system. Subsequently, electrospraying was scaled up using the industrial NANOSPIDER™ technology. The produced EGCG microparticles reduced the expression of inflammatory (IL-6, IL-8, COX-2) and catabolic (MMP1, MMP3, MMP13) mediators in pro-inflammatory 3D cell cultures. Combining the EGCG microparticles with the carrier showed a trend towards modulating EGCG activity/release. Electrospray upscaling was achieved, leading to particles with homogenous spherical morphologies. In conclusion, electrospray-based encapsulation of EGCG resulted in cytocompatible microparticles that preserved the activity of EGCG and showed the potential to control EGCG release, thus favoring IVD health by downregulating local inflammation. Future studies will focus on further exploring the biological activity of the developed delivery system for potential clinical use.